Playing Christ: Participation and Suffering in the Letters of Paul - Davey, Wesley Thomas (Currents in biblical research, 2019)
Paul's theology of suffering has been the subject of a spate of recent scholarly investigations. This article provides a roadmap for the burgeoning conversation, doing so by targeting two objectives. First, it offers a historical account of the origin of interest in the concept of 'participation with Christ' in the Pauline letters. The genesis of participation studies played an indispensable role in catalyzing research into Paul's perspective on suffering, as the article shows. Second, with that stage set, the article then turns to highlight authors who focus more narrowly on 'suffering as participation with Christ' in the letters of Paul. Although the current conversation about Paul's theology of suffering hosts a wide array of approaches and opinions, there is a broad consensus that Paul interprets believers' suffering as an indispensable part of what it means to be united to a crucified Lord.